(untitled) (The Pakistan Development Review, 1992)
A quite large number of developing countries in Asia, Africa, and Latin America, which are today characterised by chronic underdevelopment, general social retardation, slow social mobility, and political instability became highly prone to military interventions in politics in their initial phases of decolonization soon after World War II. These military interventions in the fragile civil polities and stagnant economies, termed by some scholars as the coup zone, are justified and legitimised on various pretexts of modernisation, democratisation, and reform; which means that the military seeks to fill the institutional vacuum when the overall civil administration of the country breaks down as a consequence of the rivalry for pelf and power between various ruling classes. Thus, the military has emerged as the most powerful institution in these countries. Some social revolutions of modern times, in China in 1949, for example, and in Cuba in 1959, were caused by endemic military interventions in the civil society.